Clinical-pathologic factors, as predictor of lymph nodes metastasis in cervical cancer stage IB and IIA (Medical Journal of Indonesia, 2004)
The aim of this study was to identify possible predictor factors of lymph node metastases in patients with cervical cancer stage IB and IIA. Study was conducted between May 1996 and December 2001. There were 183 patients of cervical cancer with FIGO Stage IB and IIA who were underwent radical hysterectomy and lymphadenectomy. From those 158 patients could be evaluated, consisting 43 patients with node metastases 115 patients without metastases. Research design was case control study. Case was patients with node metastases and control was those without node metastases. Multivariate analysis was made after bivariate analysis. On bivariate analysis age < 39 years, diameter of lesion > 4 cm, stage IIA > 4 cm, histopathology moderate and poor differentiation, blood and lymphatic vessel invasion were independent variables for node metastases with p value â¤ 0.05. However, on multivariate analysis younger age, parity â¥ 4, diameter of lesion, histopathology adenosquamous, and lymph vascular invasion (+) as independent factors for node metastases with p value â¤ 0.05. Conclusion: Younger age, parity â¥ 4, stage IIA > 4 cm, diameter of lesion, histopathology adenosquamous, and lymph vascular invasion (+) were risk factors for node metastases and can be used as predictors. (Med J Indones 2004; 13: 113-8)Keywords: cervical cancer, radical hysterectomy, node metastases, case control study, predictor